Teaching Strategies Employed by Novice and Experienced English Teachers in SMP Negeri 1 Seririt - Kintan Ayu Pramesti; Luh Putu Artini; Luh Putu Eka Sulistia Dewi (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to describe the teaching strategy preferences used by novice and experienced English teachers at SMP Negeri 1 Seririt. The focus of this study refers to the strategies recommended in the Merdeka Curriculum, which emphasizes student-centered learning and the development of 21st-century skills. The method used is qualitative research with data collection techniques through three main instruments, namely the teaching strategy checklist, observation checklist, and in-depth interview guides. Participants in this study consisted of one novice teacher and one experienced teacher. The results of the analysis show that novice teachers more often use direct, structured learning strategies, such as learning strategy training, discovery learning, and cooperative learning. This is adjusted to their limited teaching experience and the need to build classroom control. Meanwhile, experienced teachers show a preference for more flexible and project-based strategies such as project-based learning and problem-based learning. Both also appear to consistently apply affective and social strategies to build positive relationships with students. Factors that influence strategy preferences include teaching experience, availability of facilities, and student readiness and characteristics. This study provides insight into the differences in pedagogical approaches between novice and experienced teachers in the context of implementing the Merdeka Curriculum.